The effects of Co3O4 on the structure and unusual magnetism of LaCoO3. (9th March 2015) - Durand, A M; Hamil, T J; Belanger, D P; Chi, S; Ye, F; Fernandez-Baca, J A; Abdollahian, Y; Booth, C H
Abstract: Bulk La w CoO3 particles with w = 1.1, 1.0, 0.9, 0.8, and 0.7 were synthesized using starting materials with varying molar ratios of La2 O3 and Co3 O4 . The resulting particles are characterized as LaCoO3 crystals interfaced with a crystalline Co3 O4 phase. X-ray and neutron scattering data show little effect on the average structure and lattice parameters of the LaCoO3 phase resulting from the Co3 O4 content, but magnetization data indicate that the amount of Co3 O4 strongly affects the ferromagnetic ordering at the interfaces below T C ≈ 89 K. In addition to ferromagnetic long-range order, LaCoO3 exhibits antiferromagnetic behavior with an unusual temperature dependence. The magnetization for fields 20 Oe ⩽ H ⩽ 5 kOe is fit to a combination of a power law (( T − T C )/ T C ) β behavior representing the ferromagnetic long-range order and sigmoid-convoluted Curie–Weiss-like behavior representing the antiferromagnetic behavior. The critical exponent β = 0.63 ± 0.02 is consistent with 2D (surface) ordering. Increased Co3 O4 correlates well to increased ferromagnetism. The weakening of the antiferromagnetism below T ≈ 40 K is a consequence of the lattice reaching a critical rhombahedral distortion as T is decreased for core regions far from the Co3 O4 interfaces. We introduce a model that describes the ferromagnetic behavior of the interface regions and the unusual antiferromagnetism of the core regions.